Organization adjustments, job training and productivity: Evidence from Japanese automobile makers - Kenn Ariga; Masako Kurosawa; Fumio Ohtake; Masaru Sasaki; Shoko Yamane (Osaka University, Institute of Social and Economic Research (ISER), 2010)
This paper considers the demand for job training and its interaction with organization adjustments through rotation within a team and relocation across teams in response to demand and supply shocks. The analysis includes estimations of determinants of on-thejob training, and of how much such training contributes to improvements in individual productivity. We employ original assembler survey data from two Japanese automobile makers. We also investigate effects of the characteristics of workplace practices, including the behavior of foremen, on the incentives for individual assemblers to seek job training and productivity improvements.
Keywords: J24; M53; 330; job training; productivity improvement; relocation; rotation; workplace practices; Organisatorischer Wandel; Betriebliches Bildungsmanagement; Produktivität; Kraftfahrzeugindustrie; Japan